Thermostable NAD-linked secondary alcohol dehydrogenase from propane-grown Pseudomonas fluorescens NRRL B-1244. - Hou, C T (1983)
NAD-linked alcohol dehydrogenase activity was detected in cell-free crude extracts from various propane-grown bacteria. Two NAD-linked alcohol dehydrogenases, one which preferred primary alcohols (alcohol dehydrogenase I) and another which preferred secondary alcohols (alcohol dehydrogenase II), were found in propane-grown Pseudomonas fluorescens NRRL B-1244 and were separated from each other by DEAE-cellulose column chromatography. The properties of alcohol dehydrogenase I resembled those of well-known primary alcohol dehydrogenases. Alcohol dehydrogenase II was purified 46-fold; it was homogeneous as judged by acrylamide gel electrophoresis. The molecular weight of this secondary alcohol dehydrogenase is 144,500; it consisted of four subunits per molecule of enzyme protein. It oxidized secondary alcohols, notably, 2-propanol, 2-butanol, and 2-pentanol. Primary alcohols and diols were also oxidized, but at a lower rate. Alcohols with more than six carbon atoms were not oxidized. The pH and temperature optima for secondary alcohol dehydrogenase activity were 8 to 9 and 60 to 70 degrees C, respectively. The activation energy calculated from an Arrhenius plot was 8.2 kcal (ca. 34 kJ). The Km values at 25 degrees C, pH 7.0, were 8.2 X 10(-6) M for NAD and 8.5 X 10(-5) M for 2-propanol. The secondary alcohol dehydrogenase activity was inhibited by strong thiol reagents and strong metal-chelating agents such as 4-hydroxymercuribenzoate, 5,5'-dithiobis(2-nitrobenzoic acid), 5-nitro-8-hydroxyquinoline, and 1,10-phenanthroline. The enzyme oxidized the stereoisomers of 2-butanol at an equal rate. Alcohol dehydrogenase II had good thermal stability and the ability to catalyze reactions at high temperature (85 degrees C). It appears to have properties distinct from those of previously described primary and secondary alcohol dehydrogenases.